Pengaruh Pijat Punggung Terhadap Penurunan Rasa Nyeri Kala I Persalinan Normal di RS. PMC Tahun 2019 - Suheimi, Ihsan; Utari, Mona Dewi (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
The process of childbirth is synonymous with the pain that will be experienced, where the majority of childbirth is accompanied by pain. The pain during childbirth is a physiological process. Pain causes frustration and despair, leading some mothers to worry that they will not be able to endure the childbirth process. Massage is one of the non-pharmacological techniques in managing labor pain. The design used in this research is Pre-experimental with a One-group pretest-posttest approach, and the research sample consists of 30 laboring mothers in the Melati Room of PMC Hospital, selected through quota sampling. Data analysis techniques used the Wilcoxon test. The research results before receiving massage showed that the pain experienced by the respondents was mostly in the moderate category, with 17 respondents (56.7%), and after receiving massage, the pain experienced by the respondents was mostly in the mild category, with 18 respondents (60%). Based on the Wilcoxon analysis test results in the treatment group, a significant level of p was obtained at 0.000 (p<0.05%), so it can be concluded that there is an influence of applying back massage on the reduction of pain in the first stage of normal childbirth. It is hoped that the respondents will be more active in seeking information and expanding their knowledge through media or healthcare professionals regarding ways to reduce pain during the childbirth process